VERIFICA DI LIMITI


  1. lim x 4 x + 1 = 3       (R)
  2. lim x 2 ( 3 x + 1 ) = 7       (R)
  3. lim x 1 ( x 2 + 1 ) = 2       (R)
  4. lim x 3 x + 1 = 2       (R)
  5. lim x + ln ( x + 1 x ) = 0       (R)
  6. lim x + ln ( x x + 1 ) = 0       (R)
  7. lim x + 2 x 2 x 2 + 1 = 2       (R)
  8. lim x + ( 1 e x ) = 1       (R)
  9. lim x 2 ln ( 4 x 2 ) =       (R)
  10. lim x 1 + ln ( x + 1 ) =       (R)
  11. lim x 3 + x + 1 x 3 = +       (R)
  12. lim x 0 x 1 x 2 =       (R)
  13. lim x 1 + x x 1 = +       (R)
  14. lim x x 2 x + 1 =       (R)
  15. lim x + ln ( 1 + x 2 ) = +       (R)
  16. lim x + e 2 x + 3 = +       (R)